Notary's Liability for Mistakes in Writing Deeds That Have Been Made - Prasmara, Christiano Valdis; Arifullah, Achmad (Jurnal Konstatering, 2024)
This study was conducted with the aim of analyzing the legal liability of notaries for the deeds they have made and legal protection for parties who are harmed due to errors in the deed. This study uses a normative legal approach with a clinical legal research method that focuses on the study of applicable laws and regulations and legal norms. The data sources used are secondary data through literature studies covering primary, secondary, and tertiary legal materials. The results of the study indicate that based on Article 65 of the Notary Law No. 30 of 2004 concerning the Position of Notary in conjunction with Law No. 2 of 2014 concerning the Position of Notary, namely that notaries, both those who are still active and those who have retired, remain responsible for the deeds they have made. Article 16 of the UUJN stipulates that notaries can be subject to sanctions for mistakes that harm other parties, either through administrative or civil sanctions in accordance with Article 1365 of the Civil Code. Deeds that are legally flawed due to negligence or violations of the law can be canceled through a court decision in accordance with Article 1320 of the Civil Code. In terms of legal protection against errors in deeds in accordance with Article 1868 of the Civil Code, it is emphasized that authentic deeds made by notaries have very strong evidentiary power. If there are errors or violations of the law in the process of making it, the deed can be considered null and void or become a deed under hand. In addition, the injured party can sue for damages based on Article 1365 of the Civil Code for unlawful acts. This study focuses on notaries who remain responsible for the deeds they have made even though they have retired. Legal protection for the injured party can be realized through the cancellation of a legally defective deed which can only be done through a court decision that has permanent legal force. Notaries who make mistakes or violations can be subject to sanctions in accordance with applicable regulations, both administrative and civil sanctions.